Literature as critique of social stratification: Unveiling the intersectionality of race, class, gender, and ethnicity in sāq al-bāmbū by Sa’ūd Al-San’ūsī - M. Syauqi Fathurrahman; Maulidarni Saputri; Atthariqul Abrar (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
Although there have been many studies on the novel Sāq Al-Bāmbū, none have highlighted the issue of social stratification. Previous studies have focused on psychology, identity, cultural hybridity, social protest, and translation problems. To fill this gap in academic studies, this article aims to discuss the issue of how social stratification is represented in the novel, specifically how the intersections of race, class, gender, and ethnicity affect the lives of marginalised characters such as José. This study uses a qualitative approach, and data are collected through close reading and textual analysis, focusing on narrative elements. The data are then analysed using the sociology of literature, specifically social stratification. The analysis reveals four main aspects of social stratification illustrated in the novel: First, citizenship-based stratification shows that José’s legal Kuwaiti citizenship does not guarantee social acceptance due to his Filipino heritage, highlighting the dominance of ethnicity and race over legal status in determining inclusion. Second, economic class-based stratification reveals the rigid class divisions in Kuwaiti society, where wealth and family background influence social status. Third, gender-based stratification emphasises the economic exploitation and limited autonomy of women, especially migrant workers like José’s mother, reflecting how patriarchal norms limit women’s roles. Finally, ethnic-based stratification illustrates the marginalisation of mixed-race individuals, like José, who face discrimination in Kuwait and the Philippines, with ethnic hierarchies shaping their social standing. The findings of this study contribute to and have implications for sociological studies in Arabic literature while offering critical insights into how literature can influence awareness and reflection on social practices in real-world contexts.